Our Experience with Infratentorial Supracerebellar (ITSC) Approach for Pineal Region Tumor Excision - Sharma, Gopal R; Bista, Prakash; Khadka, Nilam; Jha, Rajiv; Bhattachan, Maya; Joshi, Sumit; Kumar, Pawan (Nepal Journal of Neuroscience, 2016)
Pineal region tumors are rare and their incidence is less than 1% of primary CNS tumors. Varieties of tumors can be found in pineal region ranging from benign to malignant pathology. Treatment modalities ranged from biopsy to total excision of tumor. Many surgical approaches have been described in the literature, however, infratentorial supracerebellar ( ITSC ) approach is versatile and widely used by many neurosurgeons worldwide. The aim of this study is to analyze and discuss the surgical outcome of pineal region tumor using ITSC approach. Advantages and limitations of this approach will be discussed. This is a retrospective study of 10 patients who underwent microsurgical excision of pineal region masses using ITSC approach in sitting position under general anesthesia at our institute between April 2009 and March 2014. The follow up period ranged from 7 months to 5 years and outcome was measured with GOS (Glasgow Outcome Scale). There were 9 male and 1 female and age ranged from 10 to 50 years. Gross total resection was performed in all 10 cases using ITSC approach. 9 patients required VP shunt for obstructive hydrocephalus. 60% (6) had benign and 40% (4) had malignant pathology. Six patients suffered from postoperative complications which included air embolism ,pneumocephalus, pseudomeningocele and seizure. Eighty percent (8) have good recovery, 1 was severely disabled and 1 died. Advanced neurological techniques combined with neuroanesthesia, neuroimaging and postoperative critical care methods have made aggressive surgical resection a mainstay of management of pineal region tumors with excellent results. Nepal Journal of Neuroscience 12:31-37, 2015